2002
DOI: 10.1038/sj.onc.1205822
|View full text |Cite
|
Sign up to set email alerts
|

Menin uncouples Elk-1, JunD and c-Jun phosphorylation from MAP kinase activation

Abstract: Menin, a nuclear protein encoded by the tumor suppressor gene MEN1, interacts with the AP-1 transcription factor JunD and inhibits its transcriptional activity. In addition, overexpression of Menin counteracts Ras-induced tumorigenesis. We show that Menin inhibits ERK-dependent phosphorylation and activation of both JunD and the Ets-domain transcription factor Elk-1. We also show that Menin represses the inducible activity of the c-fos promoter. Furthermore, Menin expression inhibits Jun N-terminal kinase (JNK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 50 publications
2
68
0
Order By: Relevance
“…The mechanism by which Menin represses JunD is still unclear. Recently, it was suggested that Menin inhibits JunD transcriptional activity by uncoupling of MAP kinase activation from MAP kinase-mediated phosphorylation of JunD (Gallo et al, 2002). Recently, we provided direct evidence that Menin recruits HDACs through association with mSin3A, a general transcriptional corepressor (Kim et al, 2003).…”
Section: Discussionmentioning
confidence: 91%
“…The mechanism by which Menin represses JunD is still unclear. Recently, it was suggested that Menin inhibits JunD transcriptional activity by uncoupling of MAP kinase activation from MAP kinase-mediated phosphorylation of JunD (Gallo et al, 2002). Recently, we provided direct evidence that Menin recruits HDACs through association with mSin3A, a general transcriptional corepressor (Kim et al, 2003).…”
Section: Discussionmentioning
confidence: 91%
“…The recruitment of p300 derepresses JunD activity, presumably by reversing HDAC-mediated silencing of the Nur77 promoter (Kim et al, 2005). Repression of MEN1 also allows ERK2-mediated JunD phosphorylation, thus providing a pleiotropic effect (Gallo et al, 2002). The phosphorylation of JunD is dependent on repression of MEN1, but not on recruitment of p300.…”
Section: Men1 Represses Jund Activity By Two Mechanismsmentioning
confidence: 90%
“…Both of N-and C-terminal regions of MEN1 are needed for efficient JunD binding (Gobl et al, 1999). MEN1 negatively effects ERK-and JNK-dependent phosphorylation of JunD, without affecting the activation of either kinase (Gallo et al, 2002). The observation that a deletion mutant of MEN1 interferes with ERK2-dependent phosphorylation of JunD, but does not suppress phosphorylation by JNK, indicates that MEN1 affects each of these pathways by a distinct mechanism (Gallo et al, 2002).…”
Section: Men1 Represses Jund Activity By Two Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this antibody detects phospho-JunD Ser100 protein due to conserved amino-acid sequences in this region between cJun and JunD, we concluded that phosphorylation of at least Ser100 of JunD was induced by H 2 O 2 or t-BHQ treatment. JunD was shown to be activated through phosphorylation of these serines and threonine by activated ERK1/2 (Gallo et al, 2002) or JNK (Yazgan and Pfarr, 2002). We observed that H 2 O 2 but not t-BHQ activates JNK, and both H 2 O 2 and t-BHQ activate ERK1/2 in several cell lines including HepG2 (Y Tsuji, unpublished data), suggesting that H 2 O 2 may utilize JNK and ERK1/2, and t-BHQ may utilize ERK1/2 for JunD phosphorylation.…”
Section: Discussionmentioning
confidence: 99%